Analysis Of Understanding Of Sports Injury Handling In Extracurricular Students - Liza, Liza; Aljabar, Muhammad Agil; Alimuddin, Alimuddin; Syafrianto, Donal (STAMINA, 2025)
The study titled "Analysis of Understanding of Handling Sports Injuries in Extracurricular Students of Public High School 8 Padang" aims to assess the knowledge and practices related to sports injury management among students involved in extracurricular sports activities. Recognizing the significant role of sports in physical and mental health, the research highlights the risks associated with sports injuries, which can range from acute injuries like sprains and fractures to chronic conditions such as tendinitis. Using a qualitative research methodology, the study involved in-depth interviews with athletes from various sports disciplines at SMA Negeri 8 Padang. The findings reveal a diverse range of injury management practices among students, with many employing initial care techniques such as rest and ice application. However, there is a notable lack of awareness regarding proper injury management protocols and preventive measures, indicating a critical need for improved education on this topic. The results suggest that effective strategies for injury prevention and management should include structured warm-up programs, appropriate protective equipment, and enhanced technical training. The study concludes that addressing these gaps in knowledge can significantly improve the well-being and performance of student athletes, ultimately contributing to better health outcomes in school sports programs.